Early weaning and concentrate supplementation on body condition score of Mecehri ewes and lambs - Kumar, R Santosh; Ramesh, V; Kumar, K Siva; Thiruvenkadan, A K (Indian Journal of Animal Production and Management, 2018)
This study was carried out on Mecheri lambs and ewes at Mecheri Sheep Research Station. A total of 72Mecheri lambs were divided into three treatment i.e., weaned at 90 days (T1), 75 days (T2) and 60 days(T3) with 24 lambs in each treatment. Each treatment was again divided into two groups, based on theconcentrate supplementation level i.e., 1 and 1.5% of body weight and all lambs were maintained undersemi-intensive system of management. The body condition score for lambs were taken fortnight intervalup to 7 months of age and ewes body condition score was recorded at different breeding stages (lambing,weaning, mating, midgestation and subsequent lambing). The results revealed that lambs body conditionscore was not influenced by weaning ages but level of concentrate feeding had greater influence on bodycondition score of lambs. Lambs fed with 1.5% concentrate supplement group had significantly higher bodycondition score compared to 1.0% supplementation. Ewe body condition score observed during differentreproductive stages and concluded that weaning age of lambs did not have any influence on body conditionscore of ewes within period but it differed between reproductive stages. BCS of ewes was lower duringweaning and higher during mid gestation and at lambing.